Prevelence of tooth loss and its impact on the elderly - Pallegedara, P.M.M.C (My University, 2003)
The purpose of this study was to assess the digree of tooth loss and its impact among elderly living in Negimbo MOH Area.it was concluded that tooth loss was highly prevelence among the study subjects and it varied according to some of the socio demographic characteristics.but edentulism was not as high as what has been shown in the ealier studies.There was a highly significant association between tooth loss and individuals' quality of life irrespetive of their socio demography status in the commnity